Hubungan Berat Bayi Lahir dengan Kejadian Stunting pada Anak usia 6- 23 Bulan di Puskesmas Baamang Unit I Tahun 2020 - Norwidya Priansiska (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2021)
Background : WHO (World Health Organization) defines stunting as a condition of failure to thrive in toddlers due to malnutrition chronic especially in the first 1000 days of life. So the child are too short at their age. Indonesia is the second highest burden of stunting children in South East Asia and Number Fifth in the world ( RISKESDAS, 2019). Purpose : Find out the correlation baby birth weight to stunting in children aged 6-23 months at Public Health Center Baamang Unit I in 2020. Research Method : This research used Retrospective Analytic Method with Cross Sectional Design Resource. Which is done at Public Health Center Baamang I in 2020 with 98 samples of children using total samplimg technique from secondary data. Using Fisher’s Exact Test. Results : The results of Bivariat analysis using Fisher’s Exact Test from 98 respondents find out there is no significant correlation between baby birth weigth to stunting. From 98 Samples stunting children aged 6-23 months, the majority of children birth with normal weight are 88 children (89.8%) and low birth weight children are 10 (10.2%), p value of 0.327. Conclusion : at This Research we can conclusion there is no significant correlation between baby birth weight to stunting in children aged 6-23 months. Keywords : Stunting, Baby Birth Weight, Toddler